Analisis Semiotik Iklan Rokok Sampoerna A Mild (Studi Semiotik Iklan Rokok Sampoerna A Mild Versi “kita gak enakan dia seenaknya” dalam Media Televisi) - Sonaria, Andari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Semiotics is a science or method for studying signs. Advertisements contain signs that appear and produce the meaning of the message in the advertisement. The aim of this research is to analyze the implied messages in the